A Comparison of Dental Students’ Self-Assessment and Instructors’ Assessment in Competency Examinations in a Preclinical Operative Dentistry Course - Alghilan MA; Munaga S; Aldakhil A (Advances in Medical Education and Practice)
Maryam A Alghilan,1,2 Swapna Munaga,1,2 Ahmed Aldakhil2,3 1Restorative and Prosthetic Dental Sciences, College of Dentistry, King Saud Bin Abdulaziz University for Health Sciences, Riyadh, Kingdom of Saudi Arabia; 2King Abdullah International Medical Research Center, Ministry of National Guard Health Affairs, Riyadh, Kingdom of Saudi Arabia; 3Department of Epidemiology and Biostatistics, College of Public Health and Health Informatics, King Saud bin Abdulaziz University for Health Sciences, Riyadh, Kingdom of Saudi ArabiaCorrespondence: Maryam A Alghilan, Restorative and Prosthetic Dental Sciences, College of Dentistry, King Saud bin Abdulaziz University for Health Sciences, P.O. Box 3660, Riyadh, 11481, Kingdom of Saudi Arabia, Tel +966 11 4299 999 Ext. 95738, Email ghilanm@ksau-hs.edu.saObjective: Student self-assessment is a skill that is taught, assessed, and attained in education for lifelong learning. In dental education, developing self-assessment is essential during the early stages of psychomotor learning. This study compared dental students’ self-assessments and instructors’ assessments in competency examinations and evaluated the progress and potential predictors of self-assessment performance, including achievement level and gender, in a Preclinical Operative Dentistry course.Methods: The preclinical operative dentistry assessment and self-assessment records by instructors and students, respectively, were collected retrospectively from intra-semester and final examination assessment rubrics. The instructors’ scoring agreement level was measured using inter-rater reliability and intra-class correlations (ICCs). Students’ self-assessment data were compared with instructors’ assessment data, and agreement was tested using inter-rater reliability estimates. The significance level was set at 0.05.Results: Instructors were calibrated based on significant agreement (p < 0.001) between full-time and part-time instructors (ICCs = 0.888 and 0.859, respectively). A significant difference (p < 0.001) was found between instructors’ and students’ mean scores. Students’ gender was significantly associated with their evaluation of performance in the intra-semester examination (p = 0.048). Most male students (58%) overestimated their performance, while the majority (44%) of female students tend to evaluate their performance accurately. There was no significant difference in the scoring of instructors and high achievers classified in the “excellent” category (p = 0.392).Conclusion: In preclinical operative dentistry education, students’ ability to accurately self-assess the quality of their work varies, and may be predicted by gender and achievement level. Students who underestimate their performance in self-assessment tend not to show improvement in their actual performance.Keywords: assessment, dental education, dental student, operative dentistry, rubric, self-assessment